2020
DOI: 10.1002/jbm.a.36918
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive micropatterning of biomaterials for induction of endothelial progenitor cell differentiation: Acceleration of in situ endothelialization

Abstract: Synthetic grafts do not provide an appealing surface for endothelial cells to adhere and colonize the inner surface. To promote in situ endothelialization the following aspect has to be taken into account, endothelial progenitor cells (EPCs) needs to be mobilized on the surface of the graft. The surface of the graft has to be sufficiently biocompatible to create a prone environment for the EPCs to adhere, proliferate and, differentiate to form a layer and subsequently improve graft patency. In this work, two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 81 publications
4
10
0
Order By: Relevance
“…However, in this case, it turned out that, as pointed out by the supplier, the thiourea link between the fluorophore and the peptide may deteriorate over time with, on top of that, a lesser stability of the labeling molecule at the pH of the tween solution. Accordingly, the measured KRGDS surface concentration was found to be one tenth of those measured in previous studies with similar grafting procedures without tween washing 33–36 (results not shown). Accordingly, the fluorescence image of the KRGDS‐FITC grafted surface is presented only for sake of showing the homogeneity of the surface conjugation but cannot be used to ascertain the peptide surface concentration.…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…However, in this case, it turned out that, as pointed out by the supplier, the thiourea link between the fluorophore and the peptide may deteriorate over time with, on top of that, a lesser stability of the labeling molecule at the pH of the tween solution. Accordingly, the measured KRGDS surface concentration was found to be one tenth of those measured in previous studies with similar grafting procedures without tween washing 33–36 (results not shown). Accordingly, the fluorescence image of the KRGDS‐FITC grafted surface is presented only for sake of showing the homogeneity of the surface conjugation but cannot be used to ascertain the peptide surface concentration.…”
Section: Methodssupporting
confidence: 67%
“…Accordingly, the measured KRGDS surface concentration was found to be one tenth of those measured in previous studies with similar grafting procedures without tween washing [33][34][35][36] (results not shown). Accordingly, the fluorescence image of the KRGDS-FITC grafted surface is presented only for sake of showing the homogeneity of the surface conjugation but cannot be used to ascertain the peptide surface concentration.…”
Section: Surface Characterizationsupporting
confidence: 64%
See 1 more Smart Citation
“…The absorbance of desorbed dyes in the solution allowed us to assess surface carboxyl group density on the PET surface. 63 COOH densities obtained for PET, PET-activated, PET-BMP and PET-RGD samples are 30 ± 7 pmol mm −2 (∼18 COOH per nm 2 ), 20 ± 8 pmol mm −2 (∼12 COOH per mm 2 ), 13 ± 0 pmol mm −2 (∼8 COOH per mm 2 ) and 17 ± 7 pmol mm −2 (∼10 COOH per nm 2 ), respectively.…”
Section: Evaluation Of the Carboxyl Density By Using The Toluidine Bl...mentioning
confidence: 87%
“…This result is consistent with previous publications (C = 71.0 at%, O = 27.0 at%, C/O = 2.6). 36,63 A slight contamination of nitrogen (N = 0.1 at%) was detected on the PET surface. As reported by Fang et al, the components of PET mainly exist in C-C/C-H (284.8 eV), C-O (286.4 eV), and O-CvO (288.8 eV) bonding.…”
Section: Xpsmentioning
confidence: 99%